Alterations in preimplantation in vivo development after preconceptional chronic moderate alcohol consumption in female mice - Cebral, Elisa (2000)
Although many studies have explored the effects of acute or chronic ethanol exposure during the postimplantation period on embryo/fetal development, few reports have described the ethanol effects on preimplantation embryo development. Little is known about the effects of ethanol consumption prior to gestation on embryo growth. Recently, we have shown that chronic moderate ethanol intake by prepubertal female mice reduces the ovulatory response and impairs in vitro fertilization and in vitro embryo preimplantation development. The purpose of the present work was to evaluate the effects of preconceptional chronic moderate ethanol ingestion on preimplantation embryo morphology and differentiation, the timing of cleavage and embryo growth in vivo, and to determine the time pattern in which alterations appear. Prepubertal female mice were treated with 10% (w/v) ethanol for 30 days prior to conception. After inducing ovulation on day 27 and 29 of the ethanol treatment, females were mated with control males and the day of presence of vaginal plug was day 1. On day 1, a decreased percentage of normal fertilized oocytes, elevated parthenogenetic oocyte activation and unfertilized eggs with abnormal metaphase II were found in ethanol-treated, compared to control females. On day 2, while any differences in the total percentage of 2-cell embryos were observed, the treated females had a significantly higher percentage of morphologically abnormal embryos, compared to control females. On day 3, the preconceptional consumption of ethanol produced significantly reduced percentages of compacted morulae and an increased percentage of uncompacted morulae. The total percentage of morulae in the treated females was lower than in controls. On day 4, ethanol-treated females showed significantly decreased percentages of hatched attached blastocysts and increased early blastocyst and morula percentages, compared to controls. Thus, preconceptional chronic moderate ethanol ingestion by prepubertal female mice produced retarded development, impaired blastocyst hatching, abnormal embryo morphology and embryo loss by fragmentation due to alterations induced in the female gamete.